The TERT hypermethylated oncologic region predicts recurrence and survival in pancreatic cancer - Faleiro, Inês (2019)
Aim: We explore the biomarker potential of the TERT hypermethylated oncologic region (THOR) in pancreatic cancer. Materials & methods: We assessed the methylation status of THOR using the cancer genome atlas data on the cohort of pancreatic cancer (n = 193 patients). Results: THOR was significantly hypermethylated in pancreatic tumor tissue when compared with the normal tissue used as control (p < 0.0001). Also, THOR hypermethylation could distinguish early stage I disease from normal tissue and was associated with worse prognosis. Discussion: We found that THOR is hypermethylated in pancreatic tumor tissue when compared with normal tissue and that THOR methylation correlates with TERT expression in tumor samples. Conclusion: Our preliminary findings support the diagnostic and prognostic values of THOR in pancreatic cancer.